DEVELOPMENT OF EVALUATION MODEL FOR INTENSIVE LAND USE IN URBAN CENTER - OLASUNKANMI, DR.IGUGO (International Journal of Multidisciplinary Research and Studies, 2020)
Starting with exploration from the angle of urban spaces, this research was conducted by analyzing the functional areas—urban centers with the foremost highlighted contradictions in terms of intensive land use so as to develop an evaluation model for intensive land use in urban centers. supported quantitative research methods, and taking under consideration three aspects of intensive use, i.e., buildings, lands and traffic in addition as multiple evaluation factors, this paper conducted the research horizontally by means of quantitative and comparative studies on each individual factor, developed the evaluation model for intensive land use in urban centers, and analyzed the driving forces of intensive land use from the aspects of buildings, land use, roads, etc.